2020
DOI: 10.1002/ps.6107
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of the extract, fractions, and pure steroidal saponins of Trillium govanianumWall. ex D. Don for the control of diamondback moth (Plutella xylostellaL.) and aphid (Aphis craccivoraKoch)

Abstract: BACKGROUND Plutella xylostella L. is the major pest of crucifers globally, causing significant yield loss. Aphis craccivora Koch is the main sucking pest of legumes that transmit viral diseases, leading to economic yield reduction. To minimize loss due to pests, farmers/growers use synthetic insecticides frequently for their control, which led to insecticide resistance, detrimental to natural enemies of pest, environment, etc. Therefore, in this study, the insecticidal activity of plant extract, fractions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Present results also confirm the findings of other reports, where the leaf n -hexane fraction of Ricinus communis showed 92–96% mortality against Sipha flava and Melanaphis sacchari [ 44 , 45 ]. Similarly, the ethyl acetate leaf fraction in the current study was also reported more promising (LC 50 = 367.75 mg/L) than the ethyl acetate fraction of Trillium govanianum (LC 50 = 2186.3 mg/L) against A. craccivora after 96 h [ 46 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Present results also confirm the findings of other reports, where the leaf n -hexane fraction of Ricinus communis showed 92–96% mortality against Sipha flava and Melanaphis sacchari [ 44 , 45 ]. Similarly, the ethyl acetate leaf fraction in the current study was also reported more promising (LC 50 = 367.75 mg/L) than the ethyl acetate fraction of Trillium govanianum (LC 50 = 2186.3 mg/L) against A. craccivora after 96 h [ 46 ].…”
Section: Discussionmentioning
confidence: 69%
“…Preliminary screening of leaf/bark extracts, fractions, SO, and compounds was carried out at higher concentrations (5000–10,000 mg/L) for their efficacy against nymphs of A. craccivora [ 46 , 57 ]. Based on preliminary data, 5–6 concentrations were prepared and evaluated against aphids in the final bioassay experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the results of Zhou et al [ 40 ] revealed that plant derivatives of Dracocephalum integrifolium had a potential value against Aphis pomi . Extracts and fractions of Trillium govanianum indicate a promising insecticidal activity towards Plutella xylostella and Aphis craccivora larvae [ 41 ]. According to our data, the toxicity of AcF and EtF at different concentrations (60, 50, 40, 30, and 20 mg/L) AcF, and (100, 50, 40, 30, and 20 mg/L) for EtF for 24, 48, and 72 h, reflected that the lowest LC 50 value (39 mg/L) was for AcF after 72 h, and 42 mg/L for EtF.…”
Section: Discussionmentioning
confidence: 99%
“…Diamondback moth, Plutella xylostella L., is one of the most serious pests of cruciferous crops in India and the world that cause economic damage [ 1 , 2 ]. Synthetic insecticides are widely used for the control of P. xylostella all year round.…”
Section: Introductionmentioning
confidence: 99%